2005
DOI: 10.1002/mame.200500235
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Producing High Melt Strength Poly(propylene) with a Reactive Extrusion

Abstract: Summary: A new class of melt blend material was prepared by extruding a mixture of 3‐aminopropyltriethoxysilane (APTES), maleic anhydride‐grafted poly(propylene) (PP‐g‐MA) with different molecular weight and MA content and poly(propylene) powder produced with a TiCl3‐based catalyst (PP‐A). A suitable selection of PP‐g‐MA provided extremely high melt strength (MS) of resultant blend materials. Such a superior melt property was caused by the synergy between the present melt reaction and the higher molecular weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…For instance, the resin with a lower melt flow rate possessed a higher melt strength, resulting in less sagging. Furthermore, a synergistic effect of long-chain branches and the presence of higher molecular weight fractions on melt strength has been observed …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…For instance, the resin with a lower melt flow rate possessed a higher melt strength, resulting in less sagging. Furthermore, a synergistic effect of long-chain branches and the presence of higher molecular weight fractions on melt strength has been observed …”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, a synergistic effect of long-chain branches and the presence of higher molecular weight fractions on melt strength has been observed. 10 Extensional Viscosity. By controlling the molecular architecture of polyethylene (PE) chains, such as the number and distribution of olefinic comonomers and long-chain branches, as well as the MWD, the mechanical and rheological properties can be adjusted in a wide range.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As a result, different strategies have been developed for branching PP chains, the best known of which is the one starting from PP grafted with anhydride maleic (PP-g-MA). The PP-g-MA is then modified to obtain branching by reaction with amino-silane [5], amines [6], [7], or by ionic interactions [8].…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] As a result, different strategies have been developed for branching PP chains, the best known of which is the one starting from PP grafted with anhydride maleic (PP‐g‐MA). The PP‐g‐MA is then modified to obtain branching by reaction with amino‐silane, [ 5 ] amines, [ 6,7 ] or by ionic interactions. [ 8 ] In our last paper, [ 9 ] we showed that the branched structure of polymer chains can be designed from a rheological criterion based on the notion of fractal behavior (coupling of relaxation modes), which polymer chains must have for nonlinear behavior (strain hardening).…”
Section: Introductionmentioning
confidence: 99%